ANTIDIABETIC ACTIVITY TEST FOR LEAVES EXTRACT OF CASSIA SIAMEA. LAMK - Tanty, Heruna; Herlina, Tati (MATTER: International Journal of Science and Technology, 2018)
This study was investigated antidiabetic activity of n-hexane and ethylacetate fractions of Cassia siamea. Lamk by α-glucosidase inhibition method using α-glucosidase enzyme and p-nitrophenyl α-D-glycopyranoside (pNPG) as substrate. The result of alpha-glucosidase inhibition test showed that n-hexane and ethyl acetate fractions and ethanol extract were inhibited the alpha glucosidase enzyme with activity 52.319%, 42.85% and 19.100% respectively at concentration of 1000 ppm.